Analisis kemampuan memahami isi teks deskripsi dalam pembelajaran bahasa indonesia ditinjau dari teori taksonomi barret pada peserta didik kelas v - Teragifa Aulia Azzahra; Sukarno Sukarno (Didaktika Dwija Indria, 2025)
This study analyzes fifth-grade students’ reading comprehension of descriptive texts using Barrett’s Taxonomy as an analytical framework. The aims were to (1) describe the learning process for descriptive text material, (2) identify internal and external obstacles students face in comprehension, and (3) analyze students’ reading comprehension across Barrett’s five levels (literal, reorganization, inference, evaluation, appreciation). A descriptive qualitative design was used with data from classroom observation, interviews, document study, and analysis of written comprehension tests. Findings show strong performance at the literal level but lower achievement on reorganization, inferential, evaluation and appreciation levels. Obstacles include limited vocabulary, anxiety in reading, teacher-centred practices, and limited use of varied media. Recommendations include diversifying media, explicit instruction on inference strategies, and rubrics that cover all Barrett levels to inform formative feedback.